Exploring key industry attributes from online customer reviews: A systematic literature review and network analysis - Ishak, Muhamad Izaidi; Harun, Amran; Ahmad, Naveed; Muslim, Aini Khalida (IPMedia Sdn Bhd, 2025)
Various key industry attributes have been identified through customer feedback in online customer reviews, offering valuable insights for both industry practitioners and academics. However, no prior study has synthesized these findings to provide a comprehensive overview of what has been discovered and what remains unexplored. To address this gap, the present study reviews recent literature on the textual analysis of online customer reviews, synthesizes key industry attributes, and employs network analysis to identify those that are common across industries. It also highlights research gaps and proposes directions for future investigation. Following the PRISMA protocol, this review focuses on studies that applied textual analysis to online customer reviews for identifying key industry attributes. A total of 34 relevant papers were included, yielding 163 attributes across eight industries: 36 for hotels, 46 for tourism, 19 for restaurants, 20 for airlines, and 42 for other sectors. At the individual industry level, staff were found to be crucial in the hotel sector; tour, recommend, and experience were significant in tourism; food emerged as a critical attribute in restaurants; and flight and staff were essential in the airline industry. To explore cross-industry patterns, network analysis was conducted using Gephi (version 0.10.1), which identified 23 common key industry attributes. The most prominent among these were service, experience, staff, food, price, and location. This study is among the first to systematically review recent research on the textual analysis of online customer reviews while integrating network analysis as part of the synthesis process. The findings offer practical insights for enhancing strategic business performance and provide a valuable foundation for future research in this area.